P57 Immune mechanisms in Pigeon Fancier's Lung. (12th November 2015) - Hasan, S; Bourke, S; Kakkar, N; Heaps, A; McSharry, C; Todryk, S
Abstract : Background: Pigeon fanciers have a 1 in 10 risk of developing Pigeon Fancier's Lung (PFL), a form of hypersensitivity pneumonitis due to inhaled pigeon antigens. This manifests as acute episodes of breathlessness, cough and fever after antigen exposure, which may progress to chronic dyspnoea and lung fibrosis. The precise disease mechanisms are unclear but both antibody and T cell responses specific for pigeon antigens are implicated. We wish to better understand immune responses against pigeon antigens in PFL to give new insight into the disease mechanisms and provide disease markers. Methods: We studied the antibody and cellular immune response in fanciers attending pigeon shows. 77 completed a questionnaire of symptoms, performed spirometry and gave a blood sample, 32 of whom had symptoms of acute PFL. Peripheral Blood Mononuclear Cells and serum were extracted from the blood, and T cell and antibody responses were measured against pigeon serum and mucin using in-house well-characterised assays (ELISA and ELIspot, respectively), as well as flow cytometry and multiplex cytokine assays. These provided quantitative outputs of specific antibody titre and reactive T cells per million PBMC, validated using positive controls. Correlations between immune responses and disease symptoms were analysed. Results: All fanciers examined had significant antibody and T cell responses against pigeon serum and/or pigeon mucin antigen. A range of antibody avidities and isotypes were observed (Figure 1 ; n = 37; 2012 cohort), but only IgA appeared to correlate with symptoms score (p = 0.012). T cell responses to pigeon serum were measured in the form of proliferating cells positive for lung-homing receptors (alpha4beta1 integrin), and secreting gamma-interferon and large amounts of anti-inflammatory interleukin 10; but did not correlate with symptoms. Conclusions: Pigeon fanciers have high levels of antigen exposure and demonstrate intense antibody and cellular immune responses, but these correlate minimally with clinical symptoms. The pathogenesis of PFL is complex and may involve an inflammatory cell-antibody axis.